Fabricating Acetic Acid Sensors Using PVP Nanofibrous Scaffold Doubly Decorated with Mesoporous Graphene - Paolo Papa; Emiliano Zampetti; Corrado Di Natale; Fabrizio De Cesare; Giovanna Tranfo; Antonella Macagnano (Proceedings)
A nanofibrous layer of polyvinylpyrrolidone (PVP) was designed to house, both in the fiber core and onto its outer surface, nanoparticles of mesoporous graphene (MGC), which are able to selectively adsorb acetic acid vapors. When grown on interdigital fingers microelectrodes (IDEs), upon UV-light irradiation taking place in air, the layer proved conductive and stable. Electrical and sensing features were significatively modulated by decorating the fiber surface with MGC (a sandwich-like structure) and polyethyleneimine (PEI). MGC, used both as a conductive filler and to decorate the fiber surface, strengthened the PVP scaffold and acted as a nucleation center for entrapping molecules of acetic acid. PEI improved the adhesion of MGC onto the surface. A preliminary study reported fast responses, high sensitivity with good linearity, selectivity, reversibility, and repeatability towards the acetic acid in ranges of up to hundreds of ppm at room temperature.